The celebrity talk show: Norms and practices. (December 2015) - Loeb, Laura
Abstract: Celebrity talk shows are a major but relatively unexplored form of broadcast talk. This article examines the norms and practices of celebrity talk show interviewing through a comparative analysis of journalistic or news interviewing. Data are drawn from four popular celebrity talk shows and three news interview programs in the U.S. The paper identifies two norms that guide talk show interactions and distinguish them from news interviews. The first norm is personalization, which allows hosts to use their own experiences and interests as a resource for questioning and responding to their guests. The second is congeniality, which fosters a predominantly friendly interviewing environment that enables guests to present both themselves and the product they are there to promote in a positive light. Although the paper is primarily concerned with elucidating these interactional norms and their implementation, it also addresses the mix of occupational concerns and market pressures that they reflect, and broader implications for the changing media landscape. Highlights: Two norms shape the celebrity talk show interview. The norm of personalization leads hosts to ask questions drawn from their own experiences. The norm of congeniality allows guests to showcase themselves and their products. Despite the pretext of casual conversation, news interviews are highly orchestrated. Understanding the norms of celebrity talk shows provides a resource for understanding the emerging hybrid genres of interviewing.